Ergonomic evaluation of the manual long handle hoes used in farm work in sandy soil in Sri Lanka - Thariq, MG; Hansika, Koongodage; Irfeey, Abdul (Journal of the Bangladesh Agricultural University, 2022)
Integrating ergonomics into the manual long handle hoe design will minimize work-related musculoskeletal disorders while improving farm workers' health and safety, consequently improving the performance. To what extent ergonomic design aspects have been incorporated into the existing manual hoe types used by farmworkers in Sri Lanka for different purposes for different soil conditions are unknown. This study used farmworkers as subjects to investigate the ergonomics of five different existing hoe types under sandy soil conditions at Ampara district in Sri Lanka. It was found that the hoe type B, which is found with a longer handle (123 cm), smaller blade size (width-21.4 cm and length- 16.3 cm), less weight (1.8 kg) and blade to handle angle of 70°is the most suitable among all the hoe types tested for hoeing operations in sandy soil. The study also found that farmworkers can discriminate between hoe types based on their suitability for the task. The study suggests that further research works are needed to evaluate the existing hoe types to use in different soils for different purposes, which will help improve the hoe type and improve farm workers' health and performance.